2004
DOI: 10.1002/pca.758
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the essential oil content and composition in leaves from cultivated plants of Hypericum androsaemum L.

Abstract: The amount and composition of the essential oil from leaves of Hypericum androsaemum L. cultivated in Arouca (Portugal) were determined in six samples harvested during 1 year at intervals of 2 months. The seasonally dependent essential oil content ranged from 0.7 mg/g biomass dry weight in September to 3.4 mg/g in February. The oil contained more than 80 compounds, 70 of which (constituting 88-93% of the total oil) were identified by GC and GC-MS. An approximation of the absolute quantification of each compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 13 publications
3
23
2
Order By: Relevance
“…The reason for this may be the plant composition. Essential oils content and composition can be greatly affected by several parameters including seasonal variation (Guedes et al, 2004), phenological cycle (Schwob et al, 2004) and geographic distribution. Cai et al, (2004) reported that free radical scavenging abilities of plants are responsible for their curative impact against some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be the plant composition. Essential oils content and composition can be greatly affected by several parameters including seasonal variation (Guedes et al, 2004), phenological cycle (Schwob et al, 2004) and geographic distribution. Cai et al, (2004) reported that free radical scavenging abilities of plants are responsible for their curative impact against some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…quantification methods (Ghasemi Pirbalouti et al, 2013;Guedes et al, 2004;Petrakis et al, 2005;Radusiene et al, 2005;Southwell & Bourke, 2001;Teixeira et al, 2013).…”
Section: Chemical Compositionsmentioning
confidence: 99%
“…The reason for this may be the plant composition. It is known that some factors such as geographic distribution, phenological cycle and seasonal variation affect chemical content and composition of essential oils (Guedes, et al, 2004;Schwob, et al, 2004). Aligiannis et al (2001) claimed that plant materials must be classified with regard to MIC results, in our study the various extracts from M. aurea can be seen as a weak inhibitor of mastitis pathogens.…”
Section: Discussionmentioning
confidence: 83%